Synthesis of Potential Bioactive Novel 7‐[2‐Hydroxy‐3‐(1, 2, 3‐triazol‐1‐yl)propyloxy]‐3‐alkyl‐4‐methylcoumarins. (18th April 2014) - Arya, Anu; Kumar, Vinod; Mathur, Divya; Singh, Sukhdev; Brahma, Raju; Singh, Rajpal; Singh, Seema; Sharma, G. L.; Parmar, Virinder S.; Prasad, Ashok K.
<x xml:space="preserve">Abstract</x> A series of 50 novel 7‐[2‐hydroxy‐3‐(1, 2, 3‐triazol‐1‐yl)propyloxy]‐3‐alkyl‐4‐methylcoumarins had been designed and synthesized in good to excellent yields via Cu(I)‐catalyzed 1, 3‐dipolar cycloaddition reaction "click chemistry" of 7‐(3‐azido‐2‐hydroxypropyloxy)‐3‐alkyl‐4‐methylcoumarins with variety of acetylene derivatives. In turn, the precursor compound, that is, 7‐(3‐azido‐2‐hydroxypropyloxy)‐3‐alkyl‐4‐methylcoumarin, was synthesized by condensation of epichlorohydrin with 7‐hydroxy‐3‐alkyl‐4‐methylcoumarins followed by opening of the epoxide ring in the resulted 7‐epoxymethoxy‐3‐alkyl‐4‐methylcoumarins with sodium azide. All the synthesized compounds were unambiguously identified on the basis of their spectral data analyses (IR, 1H‐NMR, 13C‐NMR spectra, and HRMS).